Gross Profit Margin, Return On Assets dan Return On Equity Terhadap Harga Saham (Studi pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia) - Elliv Hidayatul Lailiyah; Baron Julianto; Ardiansyah Ahsanul Hayat (STIE Jambatan Bulan, 2022)
This study aims to determine the fundamental factors, that are Gross Profit Margin, Return On Assets, and Return On Equity affect stock prices. This research was conducted on consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2018-2020. This study uses purposive sampling with a sample of 48 companies with observation data of 144 data. The approach used to analyze the data is a quantitative method. The analytical tool used in this research is multiple linear regression test with the SPSS computer program. Based on the research that has been done, the results of this study are that GPM has a positive effect on stock prices. ROA has no effect on stock prices. ROE has a positive effect on stock prices.